2018
DOI: 10.1002/ar.24008
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Muscle Fiber‐Type Distribution in Moles

Abstract: Moles are a strictly fossorial Soricomorpha species and possess a suite of specialized adaptations to subterranean life. However, the contractile function of skeletal muscles in moles remains unclear. We compared muscle fiber‐type distribution in two mole species (the large Japanese mole and lesser Japanese mole) with that in four other Soricomorpha species that are semi‐fossorial, terrestrial, or semi‐aquatic (the Japanese shrew‐mole, house shrew, Japanese white‐toothed shrew, and Japanese water shrew). For a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Type I fibers, which are known for having a postural role (Ichikawa et al, 2018; Meyers, 2019), were found deeply situated in very small percentages ranging from 0.13 to 5.3% in PL, MG, and LG, which is comparable to the percentages reported by Williamson and Frederick (1977). It is commonly reported that Type I fibers are typically found in deeper muscle regions in mammals (Armstrong, 1980; Ryan et al, 1992).…”
Section: Discussionsupporting
confidence: 76%
“…Type I fibers, which are known for having a postural role (Ichikawa et al, 2018; Meyers, 2019), were found deeply situated in very small percentages ranging from 0.13 to 5.3% in PL, MG, and LG, which is comparable to the percentages reported by Williamson and Frederick (1977). It is commonly reported that Type I fibers are typically found in deeper muscle regions in mammals (Armstrong, 1980; Ryan et al, 1992).…”
Section: Discussionsupporting
confidence: 76%
“…In the current study, the differences observed in the muscle fibre type composition of the forelimb muscles may not be due to functional strains or environmental demands, but rather the phylogeny of the species (Álvarez & Pérez, 2019). Ichikawa et al (2019) discovered the absence of MHC IIb fibres within the muscles of two species of subterranean true moles (Eulipotyphla), whereas all subtypes of fast MHC II fibres were present in the semi‐fossorial, terrestrial and semi‐aquatic Eulipotyphla species. This suggests that the subterranean habitat may have an influence on the MHC II fibre compositions in species belonging to the same phylogenetic order.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fast movements produced for digging in subterranean mammals may influence the percentages of the subtypes of MHC II fibres, which were not evaluated in the present study. Furthermore, Ichikawa et al (2019) indicated the absence of MHC I fibres in two subterranean mole species within the order Eulipotyphla (Douady et al, 2002). Other studies performed on species belonging to Eulipotyphla confirmed the absence of slow MHC I fibres within species with different locomotor habits and suggest that it may be due to phylogenetic effects and not locomotor adaptations (Peters et al, 1999; Savolainen & Vornanen, 1995; Suzuki, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to phylogenetic differences between the rodent species as myosin isoform expression can be constrained by phylogeny (Nov ak et al, 2010). Sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis in two non-drumming, T A B L E 3 The muscle fiber composition (%) of slow (type I) and fast (type II) fibres in the hind limb muscles of Georychus capensis, Bathyergus suillus, and Cryptomys hottentotus natalensis (fibers that did not stain positively were considered fast) subterranean Japanese mole species revealed that both species only had type II fibers in their front and hind limb muscles (Ichikawa et al, 2019). Avivi, Band, Joel, Shenzer, and Coleman (2009) demonstrated that the m. gastrocnemius muscles in the subterranean, nondrumming blind mole rat (Spalax ehrenbergi) had mainly type II muscle fibers which is consistent with the results in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The fiber type composition of individual muscles varies within groups of the same species as well as different species. Where some species such as sloths (Xenarthra; Spainhower et al, 2021) and Japanese moles (Mogera species; Ichikawa et al, 2019) express a single MHC isoform within a whole muscle, other species express all four muscle isoforms with variations in proportion in a single muscle. These differences in muscle fiber phenotype can be attributed to sex, age, hormonal, neural and phylogenetic influences (Nov ak, Zacharova, & Soukup, 2010;Schianffino & Reggiani, 2011).…”
mentioning
confidence: 99%